PROBLEMS OF SOCIAL INTEGRATION FOR CHILDREN WITH SEVERE SPEECH DISORDERS - Karlibaeva, Juldiz Amangeldievna; Otajonova, Gulyor Alisherovna (SCIENCE and SOCIETY, 2026)
This article explores the integration of children with severe speech impairments into society, focusing on their communicative development and social adaptation. The study is based on descriptive and observational methods. The results show that early speech therapy and inclusive education significantly improve socialization and communication skills. In addition, cooperation between parents and teachers plays a key role. In conclusion, effective integration requires early intervention, inclusive environments, and a comprehensive support approach.